Polyamines in tea processing - Palavan Ünsal, Narçin; Terzioğlu, Salih; ARISAN, ELİF DAMLA (TAYLOR & FRANCIS LTD, 4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND, 2007)
The distribution of dietary polyamines, putrescine, spermidine and spermine, was determined during processing of Camellia sinensis. Black tea manufacture is carried by a series of processes on fresh tea leaves involving withering, rolling, fermentation, drying and sieving. The aim of this research was to determine the effect of tea processing on the polyamine content in relation with antioxidant enzymes, superoxide dismutase, lipid peroxidase and glutathione peroxidase. Before processing, the spermine content was much higher than the putrescine and spermidine content in green tea leaves. Spermine was significantly decreased during processing while the putrescine and spermine contents increased during withered and rolling and decreased in the following stages. The superoxide dismutase activity increased at the withering stage and declined during processing. The transcript level of the polyamine biosynthesis-responsible enzyme ornithine decarboxylase was reduced during each processing step. This study reveals the importance of protection of nutritional compounds that are essential for health during the manufacturing process.
Keywords: Polyamines; Tea Processing; Green Tea; Antioxidant Enzymes; Ornithine-Decarboxylase; Cancer Chemoprevention; Dietary Polyamines; Black Tea; In-Vitro; Stress; Inhibition; Stomach; System; Poliaminler; Çay İşleme; Yeşil Çay; Antioksidan Enzimler; Ornitin Dekarboksilaz; Diyet poliaminler; Siyah Çay; Stres; Engelleme; Mide; Sistem